CONVERSION OF DURIAN SHELL AGROINDUSTRIAL WASTE INTO VARIOUS VALUABLE PRODUCTS TO SUPPORT THE FOOD SECURITY DURING THE COVID-19 NEW NORMAL ERA: REVIEW - Kusumaningtyas, Ratna Dewi; Syah, Ahmad Faiz Armiano (Jurnal Teknologi Hasil Pertanian, 2020)
Durian (Durio zibethinus Murray) is a tropical, delicious and expensive fruit with specific aroma. Indonesia is among the biggest and the best durian fruit producer in the world. There are various types of Durian in Indonesia, coming from different areas. Based on the data released by the Central Bureau of Statistic, it was demonstrated that the main provinces producing durian in 2019 were East Java, Central Java, West Java, North Sumatera, West Sumatera, Banten, South Sulawesi, and South Sumatera with the total harvest of  289,334 ton, 172,939 ton,  94,183 ton, 90,105 ton, 62,564 ton, 46,436 ton, 45,729 ton, and 42,048 ton, respectively. The high production of durian fruit is beneficial for the agroindustrial and economic sectors. On the other hand, it also results in the abundance waste during the harvest time which causes many problems to the environment. The percentage of durian flesh of fruit is only 20.52%, meaning that the 79.48% of durian is unutilized parts such as shell and seeds. The waste resulted from durian is about 556,360 ton per year. Durian waste, especially durian shell, is difficult to degrade. Hence, the proper waste management of the durian shell is crucial. The strategic way to manage the durian shell is by upgrading this waste into various valuable products. In this work, the innovation of the durian shell waste conversion into diverse product to support the national food security during the covid-19 new normal era is discussed.  Durian shell is potential to be used for the production of food products such as candy, pectin, edible film, and crackers, flour, and noodle. It also has potency to be utilized in the production of products which support the development of food crop agriculture and animal husbandry, such as biopesticides, organic fertilizer, and animal feed, which strongly associated with the food supply security.